Islamic Thought Of Human Rights: Malaysian Issues And Challenges, - Endut, M. Nuri Al Amin; Hamat, M. Fauzi; Sabdin, Mashitah (2008)
Islam has set distinguish fundamental outlines with regards to human rights issues through various Quranic discussions and assertions on the principle of human nobility. However, the general perception of human rights is commonly viewed from the western secular perspective which emphasizes on the fight for human freedom and equality without having any attachment to religious concern. Thus, this paper will discuss several main issues of human rights from Islamic perspective and its forms of challenges faced by Muslims particularly in Malaysia. In doing so there would be a few basic questions which needed to be answered: Does man actually have fundamental rights? Does man really enjoy human rights without being governed by any religion or law? How does Islam perceive human rights? How does man enjoy human rights while embracing Islam and worshiping Allah SWT? Would, for example, a man who has managed to free himself from the clutches of the church be thought of as a man free to enjoy his rights while being engulfed in secularism and liberalism which are in turn controlled by desires? The parameters of this paper will only include matters mentioned above and explain the status of human rights from the global and Islamic point of views. Uncertainty on human rights issues will be resolved and explained particularly in the misconception on how Islam oppresses human rights.